A comparative analysis of the correlations between section 12 of the Competition Act 89 of 1998 and section 2 of the Companies Act 71 of 2008 - Van Heerden, C.M. (Corlia) (University of Pretoria, 2017)
Mini Dissertation (LLM)--University of Pretoria, 2016.